The psychological treatment of depression : a guide to the theory and practice of cognitive behaviour therapy - Williams, J. Mark G. (Routledge, 1992)
A practical guide to the wide range of cognitive behavioural therapy techniques used in the assessment and treatment of depression, describing them in usable detail and setting them in the context of current theories of depression.